Grown-in Defects of InSb Crystals: Models and Computation (Communications in Computational Physics, 2006)
In this paper, we present a model for grown-in point defects inside indiumantimonide crystals grown by the Czochralski (CZ) technique. Our model is similar tothe ones used for silicon crystal, which includes the Fickian diffusion and a recombination mechanism. This type of models is used for the first time to analyze grown-in pointdefects in indium antimonide crystals. The temperature solution and the advance of themelt-crystal interface, which determines the time-dependent domain of the model, arebased on a recently derived perturbation model. We propose a finite difference methodwhich takes into account the moving interface. We study the effect of thermal flux onthe point defect patterns during and at the end of the growth process. Our results showthat the concentration of excessive point defects is positively correlated to the heat fluxin the system.